Business AnalysisOf Fish Cultivation (Wallagosp) In Chinese Village Chinese Size Of Beauty Regency Kampar Provinsi Riau - Ummu Salamah; Darwis Darwis; Hazmi Arif (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            This research was conducted on March 21st until 25th 2017 in Buluh China Village, SiakHulu Sub District, Kampar District, Riau Province. This study aims to determine the amount of investment costs, income, profits and to determine the feasibility of fish farming business Tapah in the Village Buluh China SiakHuluSubdistrict Kampar Riau Province. The method used in this research is survey method.The average investment incurred by the Tapah fish farmers in Buluh China is Rp.28.634.071, - with the income earned is an average of Rp.35.000.000,- with an average profit of Rp.12.402.143,- per harvest. Feasibility analysis obtained is the average value of Revenue Cost of Ratio (RCR) 1,55 then the fish farming business Tapah in the village of Buluh China is worth to continue. With the averageFinancial Rate of Return (FRR) value is 39,74 and the average Payback Period of Capital(PPC) value of  3,21 is the repayment period of Tapah fish farming business in Buluh China Village is 3 years 3 months.Keywords :Business Analysis, Tapah Fish, Chinese Buluh Village, Feasible